SEM-PLS Analysis of Factors Affecting the Effectiveness of English Course Online Learning during Covid-19 Pandemic - Ely Trianasari; Ika Yuniwati; Made Detri Suryantini (Universitas Pendidikan Mandalika, 2022)
Online learning is an alternative approach for continuing the learning process while the COVID-19 epidemic is underway. This research was undertaken to find out the factors affecting the effectiveness of English course online learning at Banyuwangi State Polytechnic during the Covid19 Pandemic. The factors studied included the quality of the media, the quality of the students, the quality of the modules/materials, the quality of the learning methods, and the quality of the tutors/trainers. The number of respondents was 259 students who were taken by using a purposive random sampling. The instruments used in this research were questionnaire and interview delivered online. The Partial Least Square (PLS) approach was used to examine this study model, which was aided by Smart PLS software. As for the results of this study, the overall p-value is smaller than 0.05, meaning that all variables have a positive influence on the effectiveness of online learning. The highest influence is from the variable of quality of students and the lowest is from the quality of tutors. The findings implicate that to deliver a successful online learning course, teachers must be able to create a new learning experience and atmosphere at each meeting through the use of diversified media, real learning resources, and appropriate learning methods in order to pique students' interest and motivate them to participate more actively in learning.